Evaluation of a Novel Spine and Surface Topography System for Dynamic Spinal Curvature Analysis during Gait - Betsch, Marcel; Wild, Michael; Johnstone, Brian; Jungbluth, Pascal; Hakimi, Mohssen; Kuehlmann, Britta; Rapp, Walter (PLoS ONE, 2013)
Introduction:The assessment of spinal deformities with rasterstereography can enhance the understanding, as well as can reduce the number of x-rays needed. However, to date this technique only allows measurements under static conditions. Since it would be of great value to be able to also analyze the spine in dynamic conditions, the present study evaluated a novel rasterstereographic system.Materials and Methods:A new rasterstereographic device was evaluated in a comparison with the gold standard in motion analysis, the VICON system. After initial testing using 12 flat infrared markers adhered to a solid plate, the two systems were evaluated with the markers adhered onto the backs of 8 test subjects. Four triangles were defined using the markers, and the sides of each triangle were measured under static and dynamic conditions.Results:On the solid plate, the sides of the 4 triangles were measured with a measuring tape and then by the two optical systems. Rasterstereography showed a high accuracy in marker detection on the solid plate. Under dynamic conditions, with the subjects walking on a treadmill, the rasterstereographically-measured side lengths were compared with the lengths measured by the VICON system as an assessment of marker detection. No significant differences (p>0.05) were found between the systems, differing only 0.07-1.1% for all sides of the four triangles with both systems.Discussion:A novel rasterstereographic measurement device that allows surface and spine topography under dynamic conditions was assessed. The accuracy of this system was with one millimeter on a solid plate and during dynamic measurements, to the gold standard for motion detection. The advantage of rasterstereography is that it can be used to determine a three-dimensional surface map and also allows the analysis of the underlying spine. © 2013 Betsch et al.
CRIS-Team Scopus Importer:2022-07-20